Some I-Convergent Double Classes of Sequences of Fuzzy Numbers Defined by Orlicz Functions: Mausumi Sen, Santanu Roy - Team, Support (Thai Journal of Mathematics, 2013)
In this paper, using the concept of ideal and Orlicz function, we introduce some new classes of double sequence spaces of fuzzy numbers. We study different topological properties of these sequence spaces like completeness, solidity, symmetricity etc. Also we obtain some inclusion relation involving these sequence spaces.